Not All SAVR Are Created Equal: All the Approaches Available for Surgical Aortic Valve Replacement - Francesco Cabrucci; Serge Sicouri; Massimo Baudo; Dimitrios E. Magouliotis; Yoshiyuki Yamashita; Beatrice Bacchi; Dario Petrone; Beman Wasef; Aleksander Dokollari; Massimo Bonacchi; Basel Ramlawi (Journal of Cardiovascular Development and Disease)
Surgical Aortic Valve Replacement (SAVR) is still one of the pillars of cardiac surgery practice, and its role is evolving into a more complex operation. The competition with structural valve therapies and the urgent demand for less invasive solutions have unleashed surgeons’ creativity in adapting to these new challenges. All the possible ways to surgically replace the aortic valve are analyzed in this review. Surgical techniques, advantages and disadvantages, and key differences are listed, helping surgeons navigate the available options. Sternotomy SAVR is the benchmark, but that is becoming obsolete and, in some cases, no longer performed for teaching purposes. Mini sternotomy is the easiest way to achieve minimal invasiveness in all anatomic situations, while right anterior thoracotomy is an elegant solution mastered by fewer surgeons. Endoscopic and robotic-assisted techniques are shaping the future of SAVR, yet they still lack wide adoption. The choice of approach is mainly dictated by the anatomic features of the patient and the surgeon’s skills. A flow diagram to overcome the learning curve and advance toward more complex surgery is provided here. Mastering as many techniques as possible is paramount when offering a patient-tailored approach and performing a safe and less invasive operation.